2022
DOI: 10.3389/fonc.2022.1021558
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bromodomain-containing proteins prognostic value and expression significance based on a genomic landscape analysis of ovarian serous cystadenocarcinoma

Abstract: BackgroundOvarian serous cystadenocarcinoma (OSC), a common gynecologic tumor, is characterized by high mortality worldwide. Bromodomain (BRD)-containing proteins are a series of evolutionarily conserved proteins that bind to acetylated Lys residues of histones to regulate the transcription of multiple genes. The ectopic expression of BRDs is often observed in multiple cancer types, but the role of BRDs in OSC is still unclear.MethodsWe performed the differential expression, GO enrichment, GSEA, immune infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…REDD1 could regulate CASP2-dependent cell death of OC by inhibiting mTOR [ 25 ]. BRPF1 played a vital role in the development and progression in OC [ 26 ]. A previous study suggested RB1 as an immune-related prognostic biomarker and promising target in OC [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…REDD1 could regulate CASP2-dependent cell death of OC by inhibiting mTOR [ 25 ]. BRPF1 played a vital role in the development and progression in OC [ 26 ]. A previous study suggested RB1 as an immune-related prognostic biomarker and promising target in OC [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…ANGPTL4 protein was con rmed in the HPA database (https://www.proteinatlas.org/) [24]. LASSO regression, subtype classi cation, immune in ltration analysis, GSEA, GSVA and drug sensitivity analysis were performed according to our previous study [20,25].…”
Section: Bioinformatic Analysismentioning
confidence: 99%